A STUDY ON THE APPLICATION OF NiZnCu FERRITE AS MAGNETIC FEEDER IN ELECTROMAGNETIC TRANSMITTER - PRENGKI, PRANSISCO (2015)
Detection of hydrocarbon in shallow and deep sea water currently uses the sea bed logging (SBL) technique, which uses a transmitter to conduct an electromagnetic signal to a hydrocarbon reservoir andtravel the signal backto the receiver. The signal, which is received by the receiver, becomes weakdueto the hydrocarbon's depth. This problem exists due to the weakness in a transmitter's performance that could not travel the EM signal to the depth of the hydrocarbon location. In order to solve this problem, a magnetic feeder was attached to the transmitter (antenna) in order to increase the amount of magnetic field around the antenna. NiZnCu Ferrites material was used as a magnetic feeder due to the magnetic properties of the material. Several characterisations were done to characterise the material. Thermogravimetric (TGA), X-Ray Diffraction (XRD), Field emission Electron Scanning Microscope (FESEM) and High Transmission Electron Microscope (HRTEM) were used to study temperature of heat treatment, nanostructure and nanosize of the material.